Adopting evidence-based practice in clinical decision making : nurses' perceptions, knowledge and barriers - Mokhtar, Intan Azura (2012)
Objective: Evidence-based practice (EBP) provides nurses with a method to use critically appraised and scientifically proven evidence for delivering quality health care to a specific population. The objective of this study was to explore nurses’ awareness of,